2014
DOI: 10.1016/j.atg.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of dnaK gene from Bacillus pumilus of hot water spring origin

Abstract: A set of thermotolerant strains isolated from hot springs of Manikaran and Bakreshwar (India) were selected with an aim to isolate dnak gene which encodes DnaK protein. The gene dnaK along with its flanking region was successfully amplified from 5 different strains (4 from Bakreshwar and one from Manikaran). Restriction fragment length polymorphism (RFLP) revealed that amplicons were almost identical in sequence. The dnak gene from one representative, Bacillus pumilus strain B3 isolated from Bakreshwar hot spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The growth of Lacticaseibacillus paracasei ZFM54 is less influenced by temperature and higher frequency of TFs that may potentially bind to its promoter region to a thermoregulatory gene dnaK can play a significant role in this tolerance. A previous study has shown that in known thermotolerant Bacillus pumilus, dnaK is highly expressed (Kumar et al , 2013). Although it cannot be ruled out that there might be differences in dnaK of different species and strains and other genes present in the genome of the two isolates play synergistic or antagonistic roles in tolerance to certain temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The growth of Lacticaseibacillus paracasei ZFM54 is less influenced by temperature and higher frequency of TFs that may potentially bind to its promoter region to a thermoregulatory gene dnaK can play a significant role in this tolerance. A previous study has shown that in known thermotolerant Bacillus pumilus, dnaK is highly expressed (Kumar et al , 2013). Although it cannot be ruled out that there might be differences in dnaK of different species and strains and other genes present in the genome of the two isolates play synergistic or antagonistic roles in tolerance to certain temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…There are several genes that confer thermotolerance in both isolates which allows growth in a wide range of temperature where dnaK and dnaJ are likely responsible for this trait these genes show the highest potential to be regulated due to the association of promoter regions to multiple transcription factors (TFs) ( Figure 4a ). Both dnaK and dnaJ belong to a chaperone system in microbes known to confer wider tolerance to temperatures (Kumar et al , 2013 and Kim et al , 2021). The two isolates grow optimally at pH 5-7, however, promoter analysis of genes responsible for this trait only suggested clpB as may be responsible in differential growth in pH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several genes that confer thermotolerance in both isolates which allows growth in a wide range of temperature where dnaK and dnaJ are likely responsible for this trait these genes show the highest potential to be regulated due to the association of promoter regions to multiple transcription factors (TFs) (Figure 4a). Both dnaK and dnaJ belong to a chaperone system in microbes known to confer wider tolerance to temperatures [44,57]. The two isolates grow optimally at pH 5-7, however, promoter analysis of genes responsible for this trait only suggested clpB as may be responsible in differential growth in pH.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of L. paracasei ZFM54 is less influenced by temperature and higher frequency of TFs that may potentially bind to its promoter region to a thermoregulatory gene dnaK can play a significant role in this tolerance. A previous study has shown that in known thermotolerant Bacillus pumilus, dnaK is highly expressed [44]. Although it cannot be ruled out that there might be differences in dnaK of different species and strains and other genes present in the genome of the two isolates play synergistic or antagonistic roles in tolerance to certain temperatures.…”
Section: Tolerance In Different Conditionsmentioning
confidence: 97%